2010
DOI: 10.1186/1471-2407-10-45
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic stratification of patients with advanced renal cell carcinoma treated with sunitinib: comparison with the Memorial Sloan-Kettering prognostic factors model

Abstract: BackgroundThe treatment paradigm in advanced renal cell carcinoma (RCC) has changed in the recent years. Sunitinib has been established as a new standard for first-line therapy. We studied the prognostic significance of baseline characteristics and we compared the risk stratification with the established Memorial Sloan Kettering Cancer Center (MSKCC) model.MethodsThis is a retrospective analysis of patients treated in six Greek Oncology Units of HECOG. Inclusion criteria were: advanced renal cell carcinoma not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 28 publications
5
19
1
1
Order By: Relevance
“…In this study, although MSKCC scores had been previously identified as prognostic in patients treated with cytokines, these factors were significantly or marginally associated with poor OS (Table 2). This is similar to recent reports that have identified patients who are more likely to benefit from the tyrosine kinase inhibitors [12][13][14]. Their results suggest that MSKCC scores are associated with the behavior of the disease rather than with a specific form of therapy.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, although MSKCC scores had been previously identified as prognostic in patients treated with cytokines, these factors were significantly or marginally associated with poor OS (Table 2). This is similar to recent reports that have identified patients who are more likely to benefit from the tyrosine kinase inhibitors [12][13][14]. Their results suggest that MSKCC scores are associated with the behavior of the disease rather than with a specific form of therapy.…”
Section: Discussionsupporting
confidence: 90%
“…In an initial analysis of 109 patients, we identified PS, time from diagnosis and number of metastatic sites as independent predictors of survival (Bamias et al , 2010). The combination of these factors led to the development of a prognostic model with similar performance with that of the more complex MSKCC model.…”
mentioning
confidence: 99%
“…( 28 ) The time from diagnosis to the start of sunitinib of <1 year, multiple metastatic sites ( P = 0.003), and poor PS were independently correlated with OS (Table 1). ( 28 )…”
Section: Biomarkers To Predict the Response To Sunitinib Therapymentioning
confidence: 98%